2007
DOI: 10.30843/nzpp.2007.60.4621
|View full text |Cite
|
Sign up to set email alerts
|

Initial establishment of the irish strain of <i>Microctonus aethiopoides</i> in New Zealand

Abstract: Four experimental releases of the parthenogenetic strain of Microctonus aethiopoides from Ireland were made in early 2006 in the Waikato Manawatu (two sites) and Hawkes Bay By early winter establishment was confirmed at all sites with parasitism levels exceeding 10 in the target host Sitona lepidus a serious pest of white clover in New Zealand Subsequent monitoring revealed considerable betweensite variation At the Hawkes Bay and Manawatu Feilding sites where overwintering weevil adults were still present in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Barker et al (1983) found clover to be the preferred diet of slugs over grasses so that in the trough experiment although slugs had the choice of existing pasture as well as newly-germinated clover seedlings, it is likely the clover seedlings were targeted by slugs. For clover root weevil it has been found that autumn adult populations in hill country near Bulls in the Manawatu peak at 20/m 2 (Gerard et al 2007), similar to the 21/m 2 used in the current study. The nematode inoculum level (412 × 10 3 /m 2 ) was comparable to levels found in Rukuhia pasture (731 × 10 3 /m 2 ) in the Waikato (Yeates et al 1983).…”
Section: Discussionsupporting
confidence: 84%
“…Barker et al (1983) found clover to be the preferred diet of slugs over grasses so that in the trough experiment although slugs had the choice of existing pasture as well as newly-germinated clover seedlings, it is likely the clover seedlings were targeted by slugs. For clover root weevil it has been found that autumn adult populations in hill country near Bulls in the Manawatu peak at 20/m 2 (Gerard et al 2007), similar to the 21/m 2 used in the current study. The nematode inoculum level (412 × 10 3 /m 2 ) was comparable to levels found in Rukuhia pasture (731 × 10 3 /m 2 ) in the Waikato (Yeates et al 1983).…”
Section: Discussionsupporting
confidence: 84%
“…At each of the Waikato and Hawke's Bay sites, 5 000 parasitised CRW adults were released, and at each of the Manawatu sites, 2 500 parasitised CRW adults were released. Establishment occurred at all sites and the populations successfully persisted through the winter (Gerard et al 2007). The remaining part of the objective was to spread the parasitoid as widely and rapidly as possible to areas where CRW was causing damage (Gerard et al 2008).…”
Section: Introductionmentioning
confidence: 92%
“…Material from the mesh sock located in the air intake tube was taken to AgResearch laboratories at Lincoln or Invermay to extract CRW adults. A sub-sample of weevils from each collection were assessed for parasitism as described in Gerard et al (2007Gerard et al ( , 2011. The remainder were counted into lots of 100, placed into 60 ml containers, and stored at 5 °C, pending distribution to farmers.…”
Section: Parasitoid Collectionmentioning
confidence: 99%
“…Adults of CRW feed on white clover leaves and can reduce establishment of seedlings, but it is the rootfeeding larvae that cause most damage by reducing nitrogen fixation and weakening or killing plants (Barratt et al 1996 and references therein;Eerens et al 2005;Gerard et al 2007). To maintain production, farmers may apply additional nitrogen fertiliser, grow more non-susceptible forage plants, and/or increase supplementary feed (White & Gerard 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation